Reflective knowledge: Knowledge extended - MI, Chienkuo (Institutional Knowledge at Singapore Management University, 2018)
In this paper, we defend the claim that reflective knowledge is necessary for extended knowledge. We begin by examining a recent account of extended knowledge provided by Palermos and Pritchard (2013). We note a weakness with that account and a challenge facing theorists of extended knowledge. The challenge that we identify is to articulate the extended cognition condition necessary for extended knowledge in such a way as to avoid counterexample from the revamped Careless Math Student and Truetemp cases. We consider but reject Pritchard’s (2012b) epistemological disjunctivism as providing a model for doing so. Instead, we set out an account of reflection informed by Confucianism and dual-process theory. We make the case that reflective knowledge offers a way of overcoming the challenge identified. We show why such knowledge is necessary for extended knowledge, while building on Sosa’s (2012) account of meta-competence.